The Implementation of participation principles in good governance - Mindarti, Lely Indah (Jurnal Ilmiah Administrasi Publik, 2016)
A shift occurs on the development paradigm from the political development orientation, citizensâ economy development paradigm up to local independence paradigm. With the participation, subsequently the development activities should be surely understood, not only considered as a responsibility but also require the citizensâ participation in order to improve their life quality. Merjosari Village has the society participation channel in a form of a neighborhood group Savings and Loan named âSrikandiâ as an opportunity for the society to improve their local economy especially family economy. Next, this paper used descriptive qualitative analysis. The result of the study showed that citizensâ participation in neighborhood Group (RT) 06, Community Group (RW) 11, Merjosari Village, Lowokwaru District, Malang in increasing the family economy through Srikandi could be seen from a forum that accommodates society participation and capability to take a part so that it can continuously progress. The emphasis of Srikandi was on the economy development through informal sectors, such as on the small-scaled industries which can give multiplier effect in increasing family economy so that local independence can be reached.